The impact of data protection laws on Chinese digital cross-border mergers and acquisitions: A quasi-natural experiment based on the EU’s general data protection regulation - Miaozhi Yu; Xiaoshuang Ye (PLoS ONE, 2026)
With the rapid growth of the digital economy, international investment activities exemplified by digital cross-border mergers and acquisitions (M&A) are increasingly active. Does the host country’s data regulation affect China’s digital cross-border M&A? This study, based on a panel dataset of Chinese digital cross-border M&A from 2009 to 2021, evaluates the impact of the European Union’s General Data Protection Regulation (GDPR) on China’s digital cross-border M&A using the PSM-DID model. The research findings indicate: (1) The implementation of GDPR significantly adversely affects Chinese enterprises engaging in digital cross-border M&A within the European Union (EU), a conclusion upheld after various robustness checks; (2) Heterogeneity analysis reveals that compared to lower-middle-income countries, high-income countries’ GDPR policies exert a more pronounced inhibiting effect on China’s digital cross-border M&A; (3) Moderation effect analysis suggests that the improvement of the digital infrastructure level, the expansion of market size, and reduction in trade costs within EU countries will mitigate GDPR’s inhibitory effect on Chinese enterprises conducting digital cross-border M&A.